A prostate utricle cyst as a cause of haematospermia in a young adult: a case report - Tupputi, Umberto; Carpagnano, Francesca Anna; Eusebi, Laura; Di Biase, Manuel; Cammarota, Aldo; Guglielmi, Giuseppe (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Prostatic utricle cyst is an embryological remnant of the Muller duct system, resulting from an incomplete regression of these structures during embryological development. Most of the time such congenital alteration is asymptomatic, but may sometimes present with various signs and symptoms, from urinary tract infections to episodes of haematospermia in a small percentage of cases. Methods: We reported the case of a 42-years-old man who suffered from recurrent episodes of haematospermia for about 20 years; the instrumental examinations, first of all TRUS and then MRI evaluation, demonstrated the presence of a cystic formation, located in the posterior median site of the prostate closely to the prostatic urethra. Results: The cytological examination on the liquid taken by transperineal US-guided fine-needle aspiration, confirmed the presence of seminal fluid and normal prostatic tissue consistent with the diagnostic hypothesis of prostatic utricle cyst. Conclusions: It’s important to recognize the imaging characteristics of the prostatic utricle cyst since it may be one of the possible benign causes of hematospermia in the young adult subject.